Adenovirus-mediated overexpression FADD induces a significant antitumor effect on human colorectal cancer cells both in vitro and in vivo - He, Xueling; Peng, Xu; Liu, Yan; Zhang, Xiaomei; Li, Hualing; Yin, Hailin (Cellular and Molecular Biology, 2018)
The Wnt/Î²-catenin signaling pathway plays important roles in cancers such as colorectal cancer. Colon cancer cells secrete and express high levels of Î²-catenin, which may stimulate autocrine signaling and further enhance activities of the canonical Wnt signaling pathway. Free Î²-catenin in the cytoplasm and nucleus leads to its association with T cell factor (TCF)/lymphocyte enhancing factor (Lef) transcription factors, and subsequent transcriptional activation of downstream target genes. FADD plays a key role in cellular apoptosis in many different types of cancer. Therefore, a recombinant adenovirus is constructed, in which an apoptosis gene FADD is placed under control of a promoter containing Tcf-responsive elements. It is observed that FADD overexpression can suppress cell growth and enhance apoptosis of SW480 cells in vitro. In addition, Ad-FADD can also suppress the growth of subcutaneous xenografts in the nude mice. Together, these results suggest that Ad-FADD has anti-proliferative and pro-apoptotic effects in colon cancer cells, which provides a novel strategy for treatment of colorectal cancer.